A Five-Year Cost-Utility Analysis Comparing Synthetic Cage Versus Allograft Use in Anterior Cervical Discectomy and Fusion Surgery for Cervical Spondylotic Myelopathy. Issue 5 (1st March 2023) - Raad, Micheal; Xu, Amy L.; Ortiz-Babilonia, Carlos; Marrache, Majd; Durand, Wesley M.; Greenberg, Marc; Jain, Amit
Abstract : Study Design: Retrospective cost-utility analysis. Objective: To conduct a cost-analysis comparing synthetic cage (SC) versus allograft (Allo) over a five-year time horizon. Summary of Background Data: SC and Allo are two commonly used interbody choices for anterior cervical discectomy and fusion (ACDF) surgery. Previous analyses comparative analyses have reached mixed conclusions regarding their cost-effectiveness, yet recent estimates provide high-quality evidence. Materials and Methods: A decision-analysis model comparing the use of Allo versus SC was developed for a hypothetical 60-year-old patient with cervical spondylotic myelopathy undergoing single-level ACDF surgery. A comprehensive literature review was performed to estimate probabilities, costs (2020 USD) and quality-adjusted life years (QALYs) gained over a five-year period. A probabilistic sensitivity analysis using a Monte Carlo simulation of 1000 patients was carried out to calculate incremental cost-effectiveness ratio and net monetary benefits. One-way deterministic sensitivity analysis was performed to estimate the contribution of individual parameters to uncertainty in the model. Results: The use of Allo was favored in 81.6% of the iterations at a societal willing-to-pay threshold of 50, 000 USD/QALY. Allo dominated (higher net QALYs and lower net costs) in 67.8% of the iterations. The incremental net monetary benefits in the Allo group was 2650 USD at a willing-to-pay threshold of 50, 000 USD/QALY. One-way deterministic sensitivity analysis revealed that the cost of the index surgery was the only factor which significantly contributed to uncertainty. Conclusion: Cost-utility analysis suggests that Allo maybe a more cost-effective option compared with SCs in adult patients undergoing ACDF for cervical spondylotic myelopathy.